Correlation of Pentosidine with Kidney Diseases in Iraqi Patients with Diabetic Nephropathy - Hamid, Ghada Salam; Allawi, Ali A.; Ghudhaib, Kadhim K. (Iraqi Journal of Science, 2021)
Diabetic nephropathy (DN) is a principle cause of microangiopathy and the main reason for kidney disease at the end stage in patients with type 2 diabetes mellitus (T2DM). This work aimed to study the relation of pentosidine with kidney injury in the case of diabetic nephropathy. This study included 75 patients suffering from T2DM and 75 apparently healthy subjects. The patients group was divided into three groups ((normoalbumin, microalbuminuria, and macroalbuminuria; 25 patients for each) on the basis of albumin-creatinine ratio (ACR) . The level of serum pentosidine was determined using an ELISA kit. The level of pentosidine was found to be significantly higher in DN patients than in the healthy group. Also, the results revealed a strong positive correlation of pentosidine with each of creatinine and blood urea levels, while a negative correlation was recorded with eGFR. It can be concluded that pentosidine may be associated with disease progression and it may be employed as one of the most efficient markers for the prediction of renal function.